Ghosts in the archive: The textual lacunæ of the Third Franklin Expedition - Kasten-Mutkus, Kathleen (Academic Commons, 2019)
The paucity of the extant written record left by the Third Franklin Expedition (1845−1848) has presented challenges to the efforts of generations of searchers and scholars. Additionally, it has underscored the reliance of Western culture on written records when establishing narratives and understanding events. This paper explores the sparse written records of the expedition in the context of their contextualisation over the years within an ersatz Franklin archive which includes a variety of discourses and documentary intents. By situating the Franklin records within an archival context, it is possible to reconsider these materials as part of a collection while also examining the ways in which they stand on their own by virtue of the (sometimes unknowable) circumstances of their creation, circulation, and preservation. Combining this archival approach with Derrida’s notion of hauntology, this paper analyses the written records of the Third Franklin Expedition as an ephemeral, and ultimately inscrutable, representation of a vanished expedition.